2022
DOI: 10.1101/2022.11.22.517520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative single-cell profiling reveals distinct cardiac resident macrophages essential for zebrafish heart regeneration

Abstract: Zebrafish exhibit a robust ability to regenerate their hearts following injury, and the immune system plays a key role in this process. We previously showed that delaying macrophage recruitment by clodronate liposome (CL) treatment compromises neutrophil resolution and heart regeneration, even when the infiltrating macrophage number was restored within the first-week post injury (Lai et al., 2017). Here, we examined the molecular mechanisms underlying the cardiac repair of regenerative PBS-control hearts vs. n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 174 publications
0
8
0
Order By: Relevance
“…Adult zebrafish are known to have populations of cTMs in the steady state and cardiac MNP populations expand following cardiac injury 24,29,62 . A recent study has highlighted the heterogeneity of resident cTMs and their involvement in promoting regeneration 42 echoing what has been described in neonatal mice 63 . However, we are yet to fully understand the spatial distribution of these cells in the heart, the roles played by distinct MNP lineages and to confirm strategies to identify these subpopulations.…”
Section: Larval Zebrafish Hearts Are Populated By Embryonic Macrophagesmentioning
confidence: 71%
See 2 more Smart Citations
“…Adult zebrafish are known to have populations of cTMs in the steady state and cardiac MNP populations expand following cardiac injury 24,29,62 . A recent study has highlighted the heterogeneity of resident cTMs and their involvement in promoting regeneration 42 echoing what has been described in neonatal mice 63 . However, we are yet to fully understand the spatial distribution of these cells in the heart, the roles played by distinct MNP lineages and to confirm strategies to identify these subpopulations.…”
Section: Larval Zebrafish Hearts Are Populated By Embryonic Macrophagesmentioning
confidence: 71%
“…Multiple studies have provided important insight into the ontogeny and maintenance of microglia 65,67,70,79 , but much of this hasn't been investigated in other tissues. Recent studies using single cell sequencing (scRNA-seq) are advancing our understanding of immune cell heterogeneity in the zebrafish heart and other organs [41][42][43]66,70 but much of this has been derived from mpeg1.1 expressing cells and is yet to be translated into new tools to define the distribution of these subpopulations. Our data indicates that using csf1ra and mpeg1.1 transgenic lines it is possible to identify four separate immune cell populations in the homeostatic heart and we have shown that these cells have distinct morphology, distribution, and behaviour in cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through scRNA-seq analysis of border zone cells, we find a population of macrophages that express genes important for remodeling and degradation of ECM, in line with recent published studies that independently corroborate the presence of this ECM macrophage cluster in the regenerating zebrafish heart 30,62 . Notably, it has been recently shown that the resident macrophage population is essential for cardiac regeneration in zebrafish 29 , and that resident macrophage populations in the neonatal and adult mouse are essential for improving functional output following multiple types of cardiac injury and disease [63][64][65] . We suggest that one function of the resident macrophage population is to promote CM invasion and replenishment of collagen-containing injured tissue with CMs during regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of immune cells in promoting the cardiac regeneration process has also been recognized in more recent years. In particular, macrophages have been shown to play an essential role in regeneration of zebrafish, salamander, and neonatal mouse hearts in response to injury [26][27][28][29] . Macrophages have been shown to directly contribute to and regulate the composition of scar/ECM in the cryoinjured heart 27,30,31 .…”
Section: Introductionmentioning
confidence: 99%